2022
DOI: 10.1371/journal.pone.0271963
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of time to full enteral feeding achievement among infants with birth weight 1000-2000g admitted to the neonatal intensive care unit of public hospitals in Hawassa city, Sidama region Ethiopian, 2019: A retrospective cohort study

Abstract: Background Nutritional care during the neonatal period is a cornerstone towards achieving optimal care. However, very limited data is available on optimizing parenteral and enteral nutrition that directly affects infant survival among Ethiopian neonates. Therefore, the objective of this study is to identify determinants of time to full enteral feeding achievement among low-birth-weight neonates admitted to neonatal intensive care units of public hospitals in Hawassa city. Methods A facility-based retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
(27 reference statements)
0
4
1
Order By: Relevance
“…This study found that the median time to full enteral feeding was 10 (95% CI: 10–11) days. This finding is higher than the studies conducted in Hawassa (8 days) [ 14 ], Addis Ababa (5 days) [ 15 ], Nigeria and Kenya (8 days) [ 17 ], the UK (8 days), and India (7 days). However, it is lower than the studies done in Italy [ 19 ] and the Netherlands [ 16 ], which found that the median survival time of full enteral feeding was 13 and 20 days, respectively.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…This study found that the median time to full enteral feeding was 10 (95% CI: 10–11) days. This finding is higher than the studies conducted in Hawassa (8 days) [ 14 ], Addis Ababa (5 days) [ 15 ], Nigeria and Kenya (8 days) [ 17 ], the UK (8 days), and India (7 days). However, it is lower than the studies done in Italy [ 19 ] and the Netherlands [ 16 ], which found that the median survival time of full enteral feeding was 13 and 20 days, respectively.…”
Section: Discussioncontrasting
confidence: 59%
“…The finding is supported by studies done in India [ 25 ], Indonesia [ 26 ], and Italy [ 19 ] which revealed a higher gestational age was associated with an earlier achievement of full enteral feeding. The study conducted in Hawassa, Ethiopia, also supported this finding, which revealed that as GA increases in a week, the time to achieve full enteral feeding decreases by 18.8% [ 14 ]. This might be due to differences in physiological maturity among these groups of neonates, in whom feeding intolerance is less common while gestational age increases due to the well-developed and matured gastrointestinal system they have [ 16 ].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations